Multi-principal-element interpenetrating network polymer, solid lubricating material and preparation method of multi-principal-element interpenetrating network polymer
Through chemical grafting and physical blending modification of multi-main interpenetrating network polymers, combined with micro/nano multi-scale structural design, a lubricated wear-reducing and wear-resistant coating was prepared, which solved the problem of material performance degradation under high temperature treatment and achieved the application effect of high mechanical properties and bonding strength at low temperatures.
Patent Information
- Application Number
- CN202510877693.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-08-29
AI Technical Summary
The performance of existing tribological polymer composite materials for high-end equipment is affected after high-temperature treatment, which is difficult to meet the mechanical performance requirements of harsh working conditions, and traditional materials are expensive.
A multi-main interpenetrating network polymer is used to prepare chemical grafting and physical blending modification, combined with micro/nano multi-scale structure design, and solid lubricant and hard nanoparticles are added to form a self-lubricating, wear-reducing and wear-resistant coating.
Cross-linking and curing at low temperatures significantly improves the mechanical properties and bonding strength of the material, meets the application needs under harsh working conditions such as low speed and high load, boundary lubrication, and extends the service life of key friction pairs.
Smart Images

Figure CN120554797A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of self-lubricating polymer composite materials, and in particular relates to a multi-principal element interpenetrating network polymer, a solid lubricating material and a preparation method thereof. Background Art
[0002] With the continuous development of China's high-end equipment, the requirements for high-performance tribological polymer composite materials used in these applications are becoming increasingly stringent. In aerospace, marine equipment, high-speed rail, and other fields, the use of synergistic lubrication using solid lubricants and greases is increasing to further reduce friction and wear in friction pairs and extend the service life of critical friction pairs.
[0003] Polymers such as phenolic resins, epoxy resins, and acrylic resins have lower curing temperatures due to the effects of modification and curing agents, but their mechanical properties struggle to meet the demands of demanding operating conditions. Materials such as polyimide and polyetheretherketone offer excellent performance, but require high-temperature sintering or curing, which is costly. The friction pair matrix properties after high-temperature treatment are affected by this heat treatment, resulting in varying degrees of tempering softening, stress release, and dimensional deformation, significantly negatively impacting product performance and manufacturing precision.
[0004] Interpenetrating network polymers (IPNs) are a special polymer blend consisting of two or more cross-linked polymers that interpenetrate and entangle with each other at the molecular level to form a unique network structure. These network structures interpenetrate and entangle with each other at the molecular level, but are not chemically bonded to each other. The key to forming an IPN is that each component must independently, simultaneously or sequentially form its own permanent cross-linked network. IPNs have excellent mechanical properties, good biocompatibility, weather resistance and degradability, and have a wide operating temperature range, making them widely used in medical, environmental protection and aerospace fields. However, multi-principal interpenetrating network polymers have not yet been applied to the field of solid lubricant technology. Summary of the Invention
[0005] Based on this, the purpose of the present invention is to provide a multi-principal element interpenetrating network polymer, a solid lubricant material and a preparation method thereof, so as to improve the mechanical properties of the solid lubricant material and not be affected by high temperature.
[0006] To solve the above problems, the technical solutions of the present invention are as follows: A method for preparing a multi-principal-element interpenetrating polymer network comprises the following steps: S11. Gradually add polyvinyl butyral resin to the solvent under stirring until the polyvinyl butyral resin is completely dissolved to form a stable and transparent slurry A; S12, adding the resin slurry obtained by mixing the high molecular weight phenolic resin and slurry A into a reaction vessel and heating it in a water bath, then dropwise adding a catalyst, and stirring the reaction to obtain a graft polymer slurry; S13, adding bisphenol A epoxy resin, benzoxazine resin, and low molecular weight liquid nitrile rubber to anhydrous ethanol and heating in a water bath, stirring and reacting to obtain a modified epoxy resin slurry; S14. Stir and mix the grafted polymer slurry and the modified epoxy resin slurry in a mass ratio of 1:(0.5-2) to obtain a multi-principal element interpenetrating network polymer slurry.
[0007] In a further embodiment, the solvent in step S11 is a mixed solvent of anhydrous ethanol and an ester or ketone solvent, and the mass percentage of anhydrous ethanol in the mixed solvent is not less than 10%.
[0008] In the present application, ketone solvents include acetone, butanone, methyl amyl ketone, methyl isobutyl ketone or cyclohexanone; ester solvents include ethyl acetate, butyl acetate or isopropyl acetate.
[0009] In a further embodiment, in step S12, the mass ratio of the high molecular weight phenolic resin to the polyvinyl butyral resin is (0.5-2):1; wherein the number average molecular weight of the high molecular weight phenolic resin is greater than 800 g / mol.
[0010] In a further embodiment, the catalyst is a silane coupling agent and urea, and the addition amount of the silane coupling agent and urea is 1-3% and 1-5% of the mass of the resin slurry, respectively; Preferably, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.
[0011] In a further embodiment, in step S12, the water bath heating temperature is 40-70° C., the stirring speed of the stirring reaction is 100-2000 r / min, and the reaction time is 0.5-12 h.
[0012] In a further embodiment, in step S13, the mass ratio of the bisphenol A epoxy resin, benzoxazine resin, low molecular weight liquid nitrile rubber, and anhydrous ethanol is 40-70:10-20:1-5:5-50; The bisphenol A epoxy resin includes E-51, E44, E-03 or NPES-901 / 904 / 907; The molecular weight of the low molecular weight liquid nitrile rubber is not greater than 20,000 g / mol.
[0013] In a further embodiment, in step S13, the water bath heating temperature is 80-100°C, the stirring speed of the stirring reaction is 100-2000 r / min, and the reaction time is 0.5-12 h; after the stirring reaction, a modified epoxy resin slurry is obtained by vacuum distillation, which is a bisphenol A epoxy resin modified with benzoxazine and low molecular weight nitrile rubber.
[0014] The second object of the present invention is to provide a multi-principal component interpenetrating network polymer, which is prepared by the above-mentioned preparation method.
[0015] The third object of the present invention is to provide a solid lubricant comprising a multi-principal interpenetrating network polymer prepared by the preparation method according to any one of claims 1 to 6, characterized in that the solid lubricant is mainly prepared from the following components in parts by mass: 100 parts of multi-principal interpenetrating polymer network; 5-50 parts of solid lubricant; 1-30 parts of hard nanoparticles.
[0016] In a further embodiment, the solid lubricant is at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyperfluoroethylene-propylene resin, ultra-high molecular weight polyethylene, graphite, boron nitride, and tungsten disulfide; The hard nanoparticles are metal carbides or metal nitrides; The particle size of the solid lubricant is 1-20 μm, and the Mohs hardness of the hard nanoparticles is ≥7 and the particle size is 10-500 nm.
[0017] In the present invention, the metal carbides include calcium carbide, boron carbide, titanium carbide, silicon carbide, chromium carbide and the like, and the metal nitrides include titanium nitride, aluminum nitride and the like.
[0018] A fourth object of the present invention is to provide a method for preparing the solid lubricant, comprising the following steps: S21, dispersing a solid lubricant in the multi-principal-element interpenetrating polymer network to obtain a mixed slurry B; S22, dispersing hard nanoparticles in mixed slurry B to obtain mixed slurry C; S23. Dilute the mixed slurry C to a viscosity of 600-1500 mPa·s to obtain a solid lubricating material.
[0019] In a further embodiment, the dilution in step S23 is performed using a diluent, and the diluent is an alcohol, an ester or a ketone.
[0020] In the present application, the diluent is preferably a mixture of anhydrous ethanol, ethyl acetate and n-methylpyrrolidone in a mass ratio of 1:1:1.
[0021] The present invention combines chemical grafting and physical blending to graft and blend-modify five polymers: polyvinyl butyral, a high molecular weight phenolic resin, a low molecular weight liquid nitrile rubber, a benzoxazine resin, and a bisphenol A epoxy resin. The high molecular weight phenolic resin is grafted with polyvinyl butyral resin, and the benzoxazine resin and low molecular weight nitrile rubber are modified on the bisphenol A epoxy resin. After physically blending the two, the polyvinyl butyral segments are "anchored" within the epoxy or phenolic resin network, resulting in an interpenetrating polymer network structure that exhibits microscopic phase separation characteristics, resulting in a multi-principal interpenetrating polymer network slurry. Molecular chain entanglement at the interface significantly enhances the mechanical properties of the material, thereby improving the strength of the multi-principal interpenetrating polymer network matrix and its adhesion to the substrate.
[0022] The present invention adds a certain solid lubricant to the modified multi-principal element interpenetrating network polymer to further improve the tribological properties of the composite material, and simultaneously adds hard nanoparticles to enhance the load-bearing capacity under high-load conditions to meet the actual working conditions requirements of key friction pairs.
[0023] Since a large amount of solid fillers are added to the multi-principal interpenetrating network polymer, in order to ensure the uniformity and surface quality of the composite material, in the actual preparation process, high-speed stirring, three-roll grinding, homogenization and sand grinding and other technical means are required to make the solid lubricant and high-hardness hard nanoparticles form a uniform and fine polymer slurry in the multi-principal interpenetrating network polymer matrix.
[0024] The present invention adopts a multi-principal interpenetrating network polymer as the matrix of the solid lubricating material, which is then coated on the surface of the key friction pair of the equipment to form a self-lubricating, wear-reducing and wear-resistant coating. It can be cross-linked and cured at a temperature lower than the tempering temperature of the metal material, and can significantly improve the wear resistance and lubrication performance of the key friction pair of the equipment, thereby greatly increasing the service life of the product and having extremely high application value.
[0025] The interpenetrating network polymer prepared by the present invention greatly improves its toughness, wear resistance, corrosion resistance and bonding strength, and has extremely strong stability and excellent adhesion under working conditions of large load and shear force.
[0026] In addition, the filler added to the interpenetrating network polymer in the present invention is designed with a micro / nano multi-scale structure, and the active construction of a nano-scale high-load-bearing, low-shear transfer film on the surface of the grinding pair is achieved by coupling the synergistic effect of micron-scale solid lubricating materials and nano-scale high-hardness particles.
[0027] The multi-principal-element interpenetrating network polymer-based solid lubricant material prepared by the present invention has a low curing temperature and is easy to construct. The finished coating has a low surface roughness, effectively promoting the formation of a lubricating oil film during boundary lubrication of the grinding pair, and can meet large-scale applications under harsh working conditions such as low speed and high load and boundary lubrication.
[0028] The solid lubricating material prepared by the present invention is coated on the surface of a workpiece by brushing, dipping, scraping, screen printing, air spraying and other process methods at an appropriate viscosity and then cured to obtain a solid lubricating material suitable for the key friction pair surfaces of high-end equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The specific embodiments of the present invention are further described in detail below with reference to the accompanying drawings: Figure 1 The friction coefficient bar graph of the lubricating materials prepared in Examples 1-3 and Comparative Examples 1-5; Figure 2 The volume wear rate bar graph of the lubricating materials prepared in Examples 1-3 and Comparative Examples 1-5; DETAILED DESCRIPTION The present invention is further illustrated below by specific examples. However, the examples and comparative examples are not intended to limit the present invention. Any similar method of the present invention and similar variations thereof should be included in the scope of protection of the present invention.
[0030] Example 1: (1) Preparation of multi-principal element interpenetrating network polymer slurry: S11. A mixed solvent consisting of 90 parts of anhydrous ethanol and 500 parts of acetone was added to a reaction vessel, and the mixture was stirred at 500 r / min using an electric stirrer. During the stirring process, 10 parts of polyvinyl butyral resin were added to the reaction vessel in 15 times for 6 hours until the polyvinyl butyral resin was completely dissolved to form a stable and transparent slurry A.
[0031] S12. Add a resin slurry obtained by mixing a high molecular weight phenolic resin (number average molecular weight of 1000 g / mol) and slurry A into a reaction vessel equipped with a thermometer and a condenser, wherein the mass ratio of the high molecular weight phenolic resin to the polyvinyl butyral resin is 2:1. After the addition is completed, nitrogen is introduced to exhaust the air and moisture in the reaction vessel. The reaction vessel is heated in a water bath at 60° C. and stirred at 500 r / min. Then, 1% by mass of the resin slurry of a silane coupling agent vinyltrimethoxysilane and 2% by mass of urea are added. The mixture is fully reacted for 8 h to obtain a graft polymer slurry. S13. Add 60 parts of epoxy resin E51, 15 parts of benzoxazine resin, 5 parts of low molecular weight liquid nitrile rubber (molecular weight 20,000 g / mol) and 20 parts of anhydrous ethanol to a three-necked flask equipped with a thermometer and a condenser. Heat to 95°C in a water bath and stir at 500 r / min. After fully reacting for 6 hours, obtain a modified epoxy resin slurry modified with benzoxazine and low molecular weight nitrile rubber by vacuum distillation.
[0032] S14. Physically mix the grafted polymer slurry and the modified epoxy resin slurry in a mass ratio of 1:1 at 25° C. and a speed of 500 r / min to obtain a multi-principal element interpenetrating network polymer slurry.
[0033] (2) Preparation of solid lubricating materials: S21. Add 10 parts of a polytetrafluoroethylene solid lubricant with a particle size of 10 μm to 100 parts of the multi-principal interpenetrating network polymer. Disperse the solid lubricant using a vacuum high-speed disperser at a stirring speed of 1500 r / min for 8 minutes, with cooling water added during the stirring process. The dispersed slurry is further mixed in a vacuum emulsification homogenizer at a vacuum level of 0.1 MPa and a rotation speed of 1800 r / min for 3 minutes to obtain a mixed slurry B.
[0034] S22. Add 10 parts of hard nanoparticles of titanium nitride with a particle size of 50 nm to the mixed slurry B. Use a vacuum high-speed disperser to disperse the hard nanoparticles at a stirring speed of 1500 r / min for 8 minutes. Cooling water needs to be passed during the stirring process. The dispersed slurry is placed in a vacuum emulsification homogenizer for further mixing at a vacuum degree of 0.1 MPa, a speed of 1800 r / min, and a time of 3 minutes to obtain a mixed slurry C.
[0035] S23. Dilute the mixed slurry C to a viscosity of about 800 mPa·s using a mixed solution of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio is 1:1:1 by mass) to obtain a solid lubricating material.
[0036] Example 2: (1) Preparation of multi-principal element interpenetrating network polymer slurry: S11. A mixed solvent of 90 parts of anhydrous ethanol and 410 parts of ethyl acetate was added to a reaction vessel, and the mixture was stirred at 500 r / min using an electric stirrer. During the stirring process, 10 parts of polyvinyl butyral resin were added to the reaction vessel in 15 times for 6 hours until the polyvinyl butyral resin was completely dissolved to form a stable and transparent slurry A.
[0037] S12. Add a resin slurry obtained by mixing a high molecular weight phenolic resin (number average molecular weight of 1000 g / mol) and slurry A into a reaction vessel equipped with a thermometer and a condenser, wherein the mass ratio of the high molecular weight phenolic resin to the polyvinyl butyral resin is 1:1. After the addition is completed, nitrogen is introduced to exhaust the air and moisture in the reaction vessel. The reaction vessel is heated in a water bath at 40° C. and stirred at a speed of 1000 r / min. Then, 2% of the mass of the resin slurry by weight of a silane coupling agent, vinyl triethoxysilane, and 5% of urea are added. The mixture is fully reacted for 12 h to obtain a graft polymer slurry. S13. Add 40 parts of epoxy resin E44, 10 parts of benzoxazine resin, 1 part of low molecular weight liquid nitrile rubber (molecular weight 20,000 g / mol) and 5 parts of anhydrous ethanol to a three-necked flask equipped with a thermometer and a condenser. Heat to 80°C in a water bath and stir at 2000 r / min. After fully reacting for 12 hours, obtain a modified epoxy resin slurry modified with benzoxazine and low molecular weight nitrile rubber by vacuum distillation.
[0038] S14. Physically mix the grafted polymer slurry and the modified epoxy resin slurry in a mass ratio of 0.5:1 at 25° C. and a speed of 500 r / min to obtain a multi-principal element interpenetrating network polymer slurry.
[0039] (2) Preparation of solid lubricating materials: S21. Add 5 parts of a 20-μm polyperfluoroethylene-propylene resin solid lubricant to 100 parts of the multi-principal interpenetrating network polymer. Disperse the solid lubricant using a vacuum high-speed disperser at a stirring speed of 1500 r / min for 8 minutes, with cooling water added during the stirring process. The dispersed slurry is further mixed in a vacuum emulsification homogenizer at a vacuum level of 0.1 MPa and a rotation speed of 1800 r / min for 3 minutes to obtain a mixed slurry B.
[0040] S22. Add 1 part of hard nanoparticle titanium carbide particles with a particle size of 10 nm to the mixed slurry B. Use a vacuum high-speed disperser to disperse the hard nanoparticles at a stirring speed of 1500 r / min for 8 minutes. Cooling water needs to be passed during the stirring process. The dispersed slurry is placed in a vacuum emulsification homogenizer for further mixing at a vacuum degree of 0.1 MPa, a speed of 1800 r / min, and a time of 3 minutes to obtain a mixed slurry C.
[0041] S23. Dilute the mixed slurry C to a viscosity of about 600 mPa·s using a mixed solution of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio is 1:1:1 by mass) to obtain a solid lubricating material.
[0042] Example 3: (1) Preparation of multi-principal element interpenetrating network polymer slurry: S11. A mixed solvent consisting of 90 parts of anhydrous ethanol and 910 parts of ethyl acetate was added to a reaction vessel, and the mixture was stirred at 500 r / min using an electric stirrer. During the stirring process, 10 parts of polyvinyl butyral resin were added to the reaction vessel in 15 times for 6 hours until the polyvinyl butyral resin was completely dissolved to form a stable and transparent slurry A.
[0043] S12. Add a resin slurry obtained by mixing a high molecular weight phenolic resin (number average molecular weight of 1000 g / mol) and slurry A into a reaction vessel equipped with a thermometer and a condenser, wherein the mass ratio of the high molecular weight phenolic resin to the polyvinyl butyral resin is 0.5:1. After the addition is completed, nitrogen is introduced to exhaust the air and moisture in the reaction vessel. The reaction vessel is heated in a water bath at 70° C. and stirred at 1500 r / min. Then, 3% of the mass of the resin slurry by weight of a silane coupling agent γ-aminopropyltriethoxysilane and 1% of urea are added. The mixture is fully reacted for 1 hour to obtain a graft polymer slurry. S13. Add 70 parts of epoxy resin NPES-901, 20 parts of benzoxazine resin, 3 parts of low molecular weight liquid nitrile rubber (molecular weight 20,000 g / mol) and 50 parts of anhydrous ethanol to a three-necked flask equipped with a thermometer and a condenser. Heat to 100°C in a water bath and stir at 100 r / min. After sufficient reaction for 1 hour, obtain a modified epoxy resin slurry modified with benzoxazine and low molecular weight nitrile rubber by vacuum distillation.
[0044] S14. Physically mix the grafted polymer slurry and the modified epoxy resin slurry in a mass ratio of 2:1 at 25° C. and a speed of 500 r / min to obtain a multi-principal element interpenetrating network polymer slurry.
[0045] (2) Preparation of solid lubricating materials: S21. Add 50 parts of a 20 μm graphite solid lubricant to 100 parts of the multi-principal interpenetrating network polymer. Disperse the solid lubricant using a vacuum high-speed disperser at a stirring speed of 1500 r / min for 8 minutes, adding cooling water during the stirring process. The dispersed slurry is further mixed in a vacuum emulsification homogenizer at a vacuum degree of 0.1 MPa and a speed of 1800 r / min for 3 minutes to obtain a mixed slurry B.
[0046] S22. Add 30 parts of hard nanoparticle silicon carbide particles with a particle size of 200 nm to the mixed slurry B, and use a vacuum high-speed disperser to disperse the hard nanoparticles at a stirring speed of 1500 r / min for 8 minutes. Cooling water needs to be passed through during the stirring process. The dispersed slurry is placed in a vacuum emulsification homogenizer for further mixing. The vacuum degree of the vacuum emulsification homogenizer is 0.1 MPa, the speed is 1800 r / min, and the time is 3 minutes to obtain a mixed slurry C.
[0047] S23. Dilute the mixed slurry C to a viscosity of about 1500 mPa·s using a mixed solution of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio is 1:1:1 by mass) to obtain a solid lubricating material.
[0048] Application Example 1: The solid lubricant prepared in Examples 1-3 was sprayed onto the surface of a CuSn12Ni2 copper alloy plate using a spray gun, wherein the compressed air pressure of the spray gun was 0.3 MPa, and the thickness of the cured coating was 20-30 μm. The plate was then cured at 140°C for 1 h and polished with 1000-mesh wet sandpaper to remove the surface oxide layer.
[0049] The friction and wear performance of the bearings was verified using an end-face friction and wear tester. The bearing element was GCr15 bearing steel with an outer diameter of 30 mm and an inner diameter of 22 mm. The coated specimens measured 40 mm × 40 mm × 1.5 mm. The total mass of the specimens was weighed before the experiment. The test conditions were: a load of 1962 N, a speed of 0.01 m / s, a test duration of 7200 s, and the lubricant was 320-grade gearbox oil. After the friction and wear experiments, the lubricant and wear debris on the sample surfaces were removed using solvents such as petroleum ether. The specimens were then placed on a high-precision balance to measure the wear mass, and the volume wear rate was calculated using a formula.
[0050] The calculation formula of volume wear rate is:
[0051] in, ΔmThe quality difference of the samples before and after the test , ρ is the density of the sample coating , F is the force applied in the normal direction , Is the rotation speed , t Rotation time .
[0052] Specific test results such as Figure 1 、 2 As shown, the friction coefficient of the solid lubricating materials prepared in Examples 1-3 tested under the same conditions is 0.07-0.09, and the volume wear rate is 0.4-1.3×10 -7 mm 3 / Nm.
[0053] Comparative Example 1: (1) Preparation of multi-principal element interpenetrating network polymer slurry is the same as in Example 1 (2) The multi-principal element interpenetrating network polymer slurry was diluted to a viscosity of about 800 mPa·s using a mixed solution of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio of 1:1:1 by mass). Then, its friction and wear properties were tested using the method of Application Example 1. The friction coefficient was 0.62 and the volume wear rate was 41×10 -7 mm 3 / Nm (such as Figure 1 、 2 shown).
[0054] Comparative Example 2: (1) Preparation of multi-principal element interpenetrating network polymer slurry is the same as in Example 1 (2) Preparation of solid lubricating materials: Add 10 parts of a 10-micron polytetrafluoroethylene solid lubricant to 100 parts of the multi-component polymer. Disperse the solid lubricant using a vacuum high-speed disperser at a stirring speed of 1500 r / min for 8 minutes, adding cooling water during the stirring process. The dispersed slurry is further mixed in a vacuum emulsifier homogenizer at a vacuum level of 0.1 MPa and a speed of 1800 r / min for 3 minutes to obtain mixed slurry B.
[0055] Mixed slurry B was diluted to a viscosity of approximately 800 mPa·s using a mixture of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio of 1:1:1 by mass). The friction and wear properties of the mixed slurry were then tested using the method of Application Example 1. The friction coefficient was 0.12, and the volume wear rate was 11×10 -7 mm 3 / Nm (such as Figure 1 、 2 shown).
[0056] Comparative Example 3: (1) Preparation of multi-principal element interpenetrating network polymer slurry is the same as in Example 1 (2) Preparation of solid lubricating materials: To 100 parts of the multi-principal element interpenetrating network polymer slurry, 10 parts of titanium nitride hard nanoparticles with a particle size of 50 nm were added. The hard nanoparticles were dispersed using a vacuum high-speed disperser at a stirring speed of 1500 r / min for 8 minutes, with cooling water added during the stirring process. The dispersed slurry was further mixed in a vacuum emulsifier homogenizer at a vacuum degree of 0.1 MPa and a speed of 1800 r / min for 3 minutes to obtain mixed slurry C.
[0057] Mixed slurry C was diluted to a viscosity of approximately 800 mPa·s using a mixture of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio of 1:1:1 by mass). The friction and wear properties of the mixed slurry were then tested using the method of Application Example 1. The friction coefficient was 0.21, and the volume wear rate was 27×10 -7 mm 3 / Nm (such as Figure 1 、 2 shown).
[0058] Comparative Example 4: 70 parts of bisphenol A epoxy resin E51 and 30 parts of thermosetting phenolic resin were added to a reaction vessel and stirred at 500 r / min using an electric stirrer until the mixture was uniform. The resin slurry was diluted to a viscosity of approximately 800 mPa·s using a mixture of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio of 1:1:1 by mass). The friction and wear properties of the slurry were then tested using the method of Application Example 1. The friction coefficient was 0.72, and the volume wear rate was 80.5×10 - 7 mm 3 / Nm (such as Figure 1 、 2 shown).
[0059] Comparative Example 5: (1) Add isophorone diisocyanate to a three-necked flask and introduce nitrogen protection. Heat the oil bath to 65 °C and dropwise add polyethylene glycol (dried in vacuo at 120 °C for 2 h). After the addition is complete, react for 1.5 h to obtain an isocyanate-terminated polyurethane prepolymer. (2) Finally, add polyethersulfone accounting for 10% of the total mass of the above polyurethane prepolymer, and stir and dissolve it evenly under a nitrogen atmosphere at 65°C to obtain component A, which is set aside; (3) Select dicyandiamide as a curing agent and dissolve it in n-methylpyrrolidone to obtain component B for standby use; (4) Component A and component B are mixed in a mass ratio of 1:1 to obtain a mixture; (5) A mixed solution of anhydrous ethanol, ethyl acetate, and n-methylpyrrolidone (mixing ratio of 1:1:1 by mass) was used to dilute the mixture to a viscosity of about 800 mPa·s. The friction and wear properties of the mixture were then tested using the method of Application Example 1. The friction coefficient was 0.63, and the volume wear rate was 55×10 -7 mm 3 / Nm (such as Figure 1 、 2 shown).
[0060] The basic principles, main features, and characteristics of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of the present invention includes the appended claims and their equivalents.
Claims
1. A method for preparing a multi-principal component interpenetrating polymer network, characterized in that: The following steps are involved: S11. Gradually add polyvinyl butyral resin to the solvent under stirring until the polyvinyl butyral resin is completely dissolved to form a stable and transparent slurry A; S12, adding the resin slurry obtained by mixing the high molecular weight phenolic resin and slurry A into a reaction vessel and heating it in a water bath, then dropwise adding a catalyst, and stirring the reaction to obtain a graft polymer slurry; S13, adding bisphenol A epoxy resin, benzoxazine resin, and low molecular weight liquid nitrile rubber to anhydrous ethanol and heating in a water bath, stirring and reacting to obtain a modified epoxy resin slurry; S14. Stir and mix the grafted polymer slurry and the modified epoxy resin slurry in a mass ratio of 1:(0.5-2) to obtain a multi-principal element interpenetrating network polymer slurry.
2. The preparation method according to claim 1, wherein: In step S11, the solvent is a mixed solvent of anhydrous ethanol and an ester or ketone solvent, and the mass percentage of anhydrous ethanol in the mixed solvent is not less than 10%.
3. The preparation method according to claim 1, wherein: In step S12, the mass ratio of the high molecular weight phenolic resin to the polyvinyl butyral resin is (0.5-2):1; wherein the number average molecular weight of the high molecular weight phenolic resin is greater than 800 g / mol.
4. The preparation method according to claim 3, wherein: The catalysts are silane coupling agent and urea, and the addition amounts of the silane coupling agent and urea are 1-3% and 1-5% of the mass of the resin slurry respectively.
5. The preparation method according to claim 4, characterized in that: The silane coupling agent is one or more of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.
6. The preparation method according to claim 1, wherein: In step S12, the water bath heating temperature is 40-70° C., the stirring speed of the stirring reaction is 100-2000 r / min, and the reaction time is 0.5-12 h.
7. The preparation method according to claim 1, wherein: In step S13, the mass ratio of the bisphenol A epoxy resin, benzoxazine resin, low molecular weight liquid nitrile rubber, and anhydrous ethanol is 40-70:10-20:1-5:5-50; The bisphenol A epoxy resin includes E-51, E44, E-03 or NPES-901 / 904 / 907; The molecular weight of the low molecular weight liquid nitrile rubber is not greater than 20,000 g / mol.
8. The preparation method according to claim 1, wherein: In step S13, the water bath heating temperature is 80-100° C., the stirring speed of the stirring reaction is 100-2000 r / min, and the reaction time is 0.5-12 h; after the stirring reaction, the modified epoxy resin slurry is obtained by vacuum distillation.
9. A multi-principal component interpenetrating network polymer, prepared by the preparation method according to any one of claims 1 to 8.
10. A solid lubricating material comprising a multi-principal element interpenetrating network polymer prepared by the preparation method according to any one of claims 1 to 6, characterized in that: It is mainly prepared from the following components in parts by mass: 100 parts of multi-principal interpenetrating polymer network; 5-50 parts of solid lubricant; 1-30 parts of hard nanoparticles.
11. The solid lubricating material according to claim 10, characterized in that: The solid lubricant is at least one of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyperfluoroethylene-propylene resin, ultra-high molecular weight polyethylene, graphite, boron nitride, and tungsten disulfide; The hard nanoparticles are metal carbides or metal nitrides; The particle size of the solid lubricant is 1-20 μm, and the Mohs hardness of the hard nanoparticles is ≥7 and the particle size is 10-500 nm.
12. The method for preparing a solid lubricating material according to claim 10 or 11, wherein: The following steps are involved: S21, dispersing a solid lubricant in the multi-principal-element interpenetrating polymer network to obtain a mixed slurry B; S22, dispersing hard nanoparticles in mixed slurry B to obtain mixed slurry C; S23. Dilute the mixed slurry C to a viscosity of 600-1500 mPa·s to obtain a solid lubricating material.
13. The preparation method according to claim 12, characterized in that: The dilution in step S23 is performed using a diluent, which is an alcohol, an ester or a ketone.